Physiotherapy strategies for functional improvement in a child with complicated hereditary spastic paraplegia: 1‐year follow‐up of a case report using a changing criterion design. - Choi, Ji‐Young; Oh, Duck‐Won; Son, Sung‐Min; Kim, Chang‐Ju (Physiotherapy Research International, 2023)
Background: and Purpose: Hereditary spastic paraplegias (HSP) are a group of clinically diverse genetic disorders that share the neurologic symptom of difficulty in walking due to progressive serious muscle weakness and spasticity in the legs. This study describes a physiotherapy program for improving the functional ability of a child diagnosed with complicated HSP and reports the treatment results. Methods: A 10‐year‐old boy with complicated HSP received a physiotherapy intervention that included strengthening of the leg muscles and treadmill training for 1 h per session, three to four times a week for 6 weeks. Outcome measures included sit‐to‐stand, 10‐m walk, 1‐min walk tests, and gross motor function measures (dimensions D and E). Results: After the intervention, the sit‐to‐stand, 1‐min walk, and 10‐m walk test scores improved by 6.75 times, 2.57 m, and 0.05 m/s, respectively. Furthermore, the gross motor function measure dimensions D and E scores improved by 8% (46%–54%) and 5% (22%–27%), respectively. The gains in each parameter were maintained at the 3‐ and 6‐month and 1‐year follow‐ups. Conclusion: These results suggest that structured physiotherapy programs can benefit the functional rehabilitation of children with complicated HSP.